Nanocrystalline Cellulose as a Versatile Engineering Material for Extrusion-Based Bioprinting - Sophia A. Read; Chee Shuen Go; Miguel J. S. Ferreira; Cosimo Ligorio; Susan J. Kimber; Ahu G. Dumanli; Marco A. N. Domingos (MDPI AG, 2023)
Naturally derived polysaccharide-based hydrogels, such as alginate, are frequently used in the design of bioinks for 3D bioprinting. Traditionally, the formulation of such bioinks requires the use of pre-reticulated materials with low viscosities, which favour cell viability but can negatively influence the resolution and shape fidelity of the printed constructs. In this work, we propose the use of cellulose nanocrystals (CNCs) as a rheological modifier to improve the printability of alginate-based bioinks whilst ensuring a high viability of encapsulated cells. Through rheological analysis, we demonstrate that the addition of CNCs (1% and 2% (w/v)) to alginate hydrogels (1% (w/v)) improves shear-thinning behaviour and mechanical stability, resulting in the high-fidelity printing of constructs with superior resolution. Importantly, LIVE/DEAD results confirm that the presence of CNCs does not seem to affect the health of immortalised chondrocytes (TC28a2) that remain viable over a period of seven days post-encapsulation. Taken together, our results indicate a favourable effect of the CNCs on the rheological and biocompatibility properties of alginate hydrogels, opening up new perspectives for the application of CNCs in the formulation of bioinks for extrusion-based bioprinting.